2010
DOI: 10.1021/jp9081867
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interaction of β-Cyclodextrin with Lipids of Varying Surface Charges: A Spectral Deciphering Using a Cationic Phenazinium Dye

Abstract: Interaction of phenosafranin (PSF), a biologically potent cationic dye molecule, has been studied with zwitterionic and anionic lipid membranes of dimyristoyl-L-alpha-phosphatidylcholine (DMPC) and dimyristoyl-L-alpha-phosphatidylglycerol (DMPG), respectively. The effect of cyclic oligosaccharide, beta-cyclodextrin (beta-CD), on the stability of these probe-bound lipid bilayers has also been investigated exploiting steady state and time-resolved fluorescence, steady state fluorescence anisotropy, and dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 55 publications
4
73
0
Order By: Relevance
“…In a different context, a detail study of the interaction of PSF with b-CD has been reported in one of our recent publications [55]. The essence of the study relevant to our present work is the value of the binding constant (K b = 82.0 l mole À1 ) for the formation of the PSF-b-CD inclusion complex.…”
Section: Psf-b-cd Interactionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a different context, a detail study of the interaction of PSF with b-CD has been reported in one of our recent publications [55]. The essence of the study relevant to our present work is the value of the binding constant (K b = 82.0 l mole À1 ) for the formation of the PSF-b-CD inclusion complex.…”
Section: Psf-b-cd Interactionmentioning
confidence: 95%
“…The essence of the study relevant to our present work is the value of the binding constant (K b = 82.0 l mole À1 ) for the formation of the PSF-b-CD inclusion complex. The low value of K b implies a partial encapsulation of the probe inside the CD cavity which is justified from the relative dimensions of PSF and b-CD cavity [55].…”
Section: Psf-b-cd Interactionmentioning
confidence: 98%
“…The lipid solution was prepared following the same method as adopted and illustrated in our previous publications [10,11]. The required amount of solid lipid was dissolved in 2:1 (v/v) chloroform:methanol mixture.…”
Section: Preparation Of the Lipidmentioning
confidence: 99%
“…1(A)) [10,13]. On addition of EYPC lipid to the aqueous buffered solution of PSF, absorbance of PSF decreases with a bathochromic shift of the band maximum.…”
Section: Steady State Absorption and Emission Studymentioning
confidence: 99%
See 1 more Smart Citation